Evaluation of the weighted level of damping of bounded disturbances in descriptor systems - Mazko, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We establish necessary and sufficient conditions for the validity of the upper bounds for the performance criteria of linear descriptor systems characterizing the weighted damping level of external and initial disturbances. The verification of these conditions is reduced to solving matrix equations and inequalities. The main statements are formulated with an aim of their subsequent application in the problems of robust stabilization and in the H_∞ -optimization problems for descriptor control systems.